2018
DOI: 10.1007/s12551-018-0415-6
|View full text |Cite
|
Sign up to set email alerts
|

Finding cancer driver mutations in the era of big data research

Abstract: In the last decade, the costs of genome sequencing have decreased considerably. The commencement of large-scale cancer sequencing projects has enabled cancer genomics to join the big data revolution. One of the challenges still facing cancer genomics research is determining which are the driver mutations in an individual cancer, as these contribute only a small subset of the overall mutation profile of a tumour. Focusing primarily on somatic single nucleotide mutations in this review, we consider both coding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The excellent literature reviews and research papers in this area cover clinical and social benefits, as well as genomic sequence analysis, pattern identification, and approaches and/ or corroboration of target discovery. This latter category produces vital software tools [8396]. Recently, functional advances were reviewed as well [97].…”
Section: Introductionmentioning
confidence: 99%
“…The excellent literature reviews and research papers in this area cover clinical and social benefits, as well as genomic sequence analysis, pattern identification, and approaches and/ or corroboration of target discovery. This latter category produces vital software tools [8396]. Recently, functional advances were reviewed as well [97].…”
Section: Introductionmentioning
confidence: 99%
“…The cBio Cancer Genomics Portal (https://www.cbioportal.org/) is an open-access resource for exploration of large cancer genomics data sets (Cerami et al, 2012; Gao et al, 2013). These datasets have allowed for comprehensive genome-wide analyses of genetic alterations in multiple tumor types (Poulos and Wong, 2018). A relatively small fraction of somatic variants known as driver mutations have considerable functional effects and can be acquired over time as a result of a range of mutational processes, rather than inherited (Haber and Settleman, 2007; Lawrence et al, 2013; Vogelstein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] Deep sequencing of different types of cancer has shown that each tumor has its own set of somatic mutations in several genes, with tumors of the same histotype and tissue origin showing great heterogeneity in their somatic mutation profiles. [ 41–43 ] Oncogenomics research is also evidencing enormous intratumoral heterogeneity, which manifests as distinct cell populations within a patient's tumor (and between a primary lesion and its metastases); intratumoral heterogeneity has been observed in various solid and hematological cancers. [ 44–46 ] These forms of tumor heterogeneity pose challenges for both diagnosis and treatment.…”
Section: Pan‐tumoral Molecular Features: Mutational Heterogeneity Andmentioning
confidence: 99%